2017
DOI: 10.1021/acs.langmuir.6b04365
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Rheology of Sterically Stabilized Colloids at Liquid Interfaces and Its Effect on the Stability of Pickering Emulsions

Abstract: Particle-laden interfaces can be used to stabilize a variety of high-interface systems, from foams over emulsions to polymer blends. The relation between the particle interactions, the structure and rheology of the interface, and the stability of the system remains unclear. In the present work, we experimentally investigate how micron-sized, near-hard-sphere-like particles affect the mechanical properties of liquid interfaces. In particular, by comparing dried and undried samples, we investigate the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 58 publications
5
53
0
Order By: Relevance
“…Layer‐by‐layer assembly was used to produce a number of interfacial coacervates based on hydrogen‐bonding polymers, in which a H‐bond‐donating polymer, e.g., poly(methacrylic acid) (PMAA) or poly(acrylic acid) (PAA), binds to a H‐bond‐accepting polymer, e.g., poly(vinylpyrrolidone) (PVP) or poly(propylene oxide) (PPO). De Baubigny et al then studied the same system but, rather than using layer‐by‐layer assembly, the polymers were initially separated in immiscible phases (i.e., oil and water) and interacted with one another at the liquid–liquid interface, in a manner similar to that used by Kaufman et al Interfacial shear rheology showed that the mechanical moduli of the H‐bonded polymer coacervates could be tuned over four orders of magnitude by varying pH (Gnormals103101 N m −1 , note that the upper limit may underestimate film strength due to the compliance of the DWR geometry) . In combination with microscopy and profilometry to measure film thickness and capsule behavior, the rheological properties of the film could then be related to capsule and emulsion structure and stability as a function of pH (Figure c,d).…”
Section: Quantitative Descriptions Of Complex Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Layer‐by‐layer assembly was used to produce a number of interfacial coacervates based on hydrogen‐bonding polymers, in which a H‐bond‐donating polymer, e.g., poly(methacrylic acid) (PMAA) or poly(acrylic acid) (PAA), binds to a H‐bond‐accepting polymer, e.g., poly(vinylpyrrolidone) (PVP) or poly(propylene oxide) (PPO). De Baubigny et al then studied the same system but, rather than using layer‐by‐layer assembly, the polymers were initially separated in immiscible phases (i.e., oil and water) and interacted with one another at the liquid–liquid interface, in a manner similar to that used by Kaufman et al Interfacial shear rheology showed that the mechanical moduli of the H‐bonded polymer coacervates could be tuned over four orders of magnitude by varying pH (Gnormals103101 N m −1 , note that the upper limit may underestimate film strength due to the compliance of the DWR geometry) . In combination with microscopy and profilometry to measure film thickness and capsule behavior, the rheological properties of the film could then be related to capsule and emulsion structure and stability as a function of pH (Figure c,d).…”
Section: Quantitative Descriptions Of Complex Interfacesmentioning
confidence: 99%
“…a) The Double Wall Ring geometry, which can be mounted on a commercial rheometer and used to probe solely the material properties of the adsorbed species. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Quantitative Descriptions Of Complex Interfacesmentioning
confidence: 99%
“…This effect was used to help explain the shape of aggregates formed by mosquito eggs at the air-water interface [19] and more recently the self-assembly of cubes at an interface [20]. Surface roughness on a particle can 20 lead to an undulating contact line, which distorts the meniscus [21] and has been used as a simple and robust way to impart emulsion stability [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…For weakly hydrophobic particles the surface shear elasticity (G') was unmeasurable and close to the sensitivity limit of the measurement technique. For weak particle networks Van Hooghten [30] emphasized that care should be taken when interpreting the viscoelastic properties of particle-laden films because the geometry inertia can lead to erroneous behaviour. As particles partition more strongly at the air-water interface the contribution from G' emerges and a strongly elastic interface eventually formed with long-range attraction attributed to hydrophobic and capillary forces.…”
Section: Introductionmentioning
confidence: 99%